Implementasi Prinsip Good Governance Terhadap Pelaporan Keuangan Pada Dinas Perumahan Rakyat Kawasan Permukiman Dan Cipta Karya Kabupaten Jember - Monica Adelia Putri; Nova Puspita Ramadhani; Nabilatul Mufidah; Siti Indah Purwaning Yuwana4 (CV. ITTC INDONESIA, 2024)
The principles of Good Governance play an important role in realizing clean government and realizing community welfare. Therefore, to achieve better governance, especially in the public housing service in residential areas and creative works, it is necessary to apply the principles of good governance in carrying out its authority, such as preparing financial reports. The purpose of this research is to find out about the implementation of Good Governance principles in financial reporting in the public housing service in residential areas and creative works of Jember district. This research uses a qualitative descriptive research method. The results of the research are that the implementation of good governance principles in the public housing service in residential areas and creative works of Jember district has been carried out well and has had a positive influence on its management.